2020
DOI: 10.29227/im-2020-02-10
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Performance of DJI Phantom 4 RTK in the PPK Mode for 3D Mapping Open-Pit Mines

Abstract: Open-pit coal mines’ terrain is often complex and quickly and frequently changes. Therefore, topographic surveys of open-pit mines are undertaken on a daily basis. While these tasks are very time-consuming and costly with traditional methods such as total station and GNSS, the unmanned aerial vehicle (UAV) based method can be more efficient. This method is a combination of the “Structure from motion” (SfM) photogrammetry technique and UAV photogrammetry which has been widely used in topographic surveying. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…This elevation error is random in a way, as it differed even in duplicate flights with the same configuration and the same UAV. This is in accordance with the findings by other authors (e.g., [34,36,38,39]), regardless of whether a fixed-wing or rotary-wing UAV was used.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This elevation error is random in a way, as it differed even in duplicate flights with the same configuration and the same UAV. This is in accordance with the findings by other authors (e.g., [34,36,38,39]), regardless of whether a fixed-wing or rotary-wing UAV was used.…”
Section: Discussionsupporting
confidence: 93%
“…A detailed analysis of the results revealed that incorrect calculation of the internal orientation elements, particularly of the focal length f, is the most likely reason for this problem (e.g., [34,38,40]). Various strategies to deal with this problem have been proposed, such as the use of oblique images (e.g., [19,36,40]), including a small number of GCPs (e.g., [36,39,40,44]) or camera pre-calibration (e.g., [34,42]). Disregarding the use of GCPs (a reliable solution which, however, negates the principal goal of this study, i.e., the simplification of the measurement by avoiding the use of GCPs), it is necessary to try to propose a measurement strategy (flight configuration, processing method, other techniques) to prevent the systematic error.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such approaches to capturing the reality are being employed in many fields, from reality modeling for identification of historical monuments [6], infrastructure mapping [7], mapping of open-pit mines [8], monitoring of changes during mining [9], coastline mapping [10], intertidal reef analysis [11], measurements for the purposes of building reconstruction [12], earthworks volume calculations [13], archaeological documentation [14], etc. Often, the data are processed to produce a general [15] or specialized [16] Digital Terrain Model (DTM).…”
Section: Introductionmentioning
confidence: 99%
“…Such approaches to capturing the reality are being employed in many fields, from reality modeling for the identification of historical monuments [6], infrastructure mapping [7], mapping of open-pit mines [8], monitoring of changes during mining [9], coastline mapping [10], intertidal reef analysis [11], measurements for the purposes of building reconstruction [12], earthworks volume calculations [13], archaeological documentation [14], etc. Often, the data are processed to produce a general [15] or specialized [16] digital terrain model (DTM).…”
Section: Introductionmentioning
confidence: 99%